Measuring the orientation of chains in polypropylene welds by infrared microscopy: A tool to understand the impact of thermo-mechanical treatment and processing. (9th March 2015) - Damodaran, Subin; Schuster, Tobias; Rode, Karsten; Sanoria, Abhishek; Brüll, Robert; Stöhr, Neda
Abstract: The superstructures developed in the welds between injection molded plates made from α-nucleated and non-nucleated isotactic polypropylene (iPP) were analyzed by infrared (IR) microscopy, polarized light microscopy (PLM) and differential scanning calorimetry (DSC). Layers of distinct structures and size formed during welding in the welds were identified by PLM. Deformation of spherulites occurred in the weld seams due to the sheared melt flow. The orientation of the polymer chains in the welds, which is the result of melting and recrystallization, was quantified by IR microscopy for the first time: In the injection molded plates the chains were oriented along machine direction (MD), whereas this pattern changed to normal direction (ND) at the weld seams. Two positions at the welds were inspected to study the orientation of the chains: In one of these the PLM image depicts two well defined weld seams, while at the other, the weld seams were absent. DSC analysis of microtomed sections revealed the presence of both iPP polymorphs in the injection molded plates, whereas in the weld seam and weld core the α- and β-phase, respectively, were found. The degree of crystallinity (Xc ) of the welds of iPP calculated using DSC and IR microscopy showed a homogeneous profile across the welds. The antioxidants (AOs) and the nucleating agent were profiled across the weld using IR-microscopy. A significant consumption of AOs during welding could be shown, and, using the principle of IR-dichroism, thermo-oxidative degradation of iPP chains was observed, even in the presence of AOs. The nucleating agent was homogeneously distributed across the weld. Graphical abstract: